Pelatihan dan Pendampingan Guru untuk Mendukung SDGs Pendidikan Berkualitas melalui Penerapan Media Pembelajaran Puzzle Etnosains untuk Mendukung Local Wisdom - Fuadi, Tuti Marjan; Hamama, Syarifah Farissi; Maulydia, Anisa; Khatimah, Husnul; Maulida, Maulida; Suryani, Suryani (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: FKIP Unsyiah Kindergarten is a kindergarten fostered by Syiah Kuala University, located at Jl. Inong Balee, PPG Dormitory, Kopelma Darussalam Village, Syiah Kuala District, Banda Aceh City, Aceh Province. There are many games that are appropriate for the children's age in the FKIP Kindergarten yard, such as swings, slides, and others. All of these games train students' psychomotor skills. Meanwhile, games that train students' cognitive skills are also in the classroom, such as LEGO and block building. The games in the FKIP Kindergarten yard are still not enough to create or even build and support knowledge related to ethnoscience in order to clarify local wisdom for students. The purpose of this community service is to provide training and mentoring for teachers in developing interactive learning media, Ethnoscience Puzzles to Support Local Wisdom. Method: This PKM activity will use 5 stages of activities, namely Socialization, Training, Technology Application, Mentoring and Evaluation, and Program Sustainability. Results: There is a 27% increase in partner capabilities. This means that teachers gained a number of new skills during the community service activities provided by the community service team, where the initial ability of the partners was 62% and after the activities, the final ability increased to 89%. Conclusion: The training and mentoring activities had a positive effect on teachers at the FKIP Unsyiah Kindergarten.